Cockayne syndrome group B protein has novel strand annealing and exchange activities - Muftuoglu, Meltem (Oxford University Press, 2006)
Cockayne syndrome (CS) is a rare inherited human genetic disorder characterized by UV sensitivity, severe neurological abnormalities and prageroid symptoms. The CS complementation group B (CSB) protein is involved in UV-induced transcription coupled repair (TCR), base excision repair and general transcription. CSB also has a DNA-dependent ATPase activity that may play a role in remodeling chromatin in vivo. This study reports the novel finding that CSB catalyzes the annealing of complementary single-stranded DNA (ssDNA) molecules with high efficiency, and has strand exchange activity. The rate of CSB-catalyzed annealing of complementary ssDNA is 25-fold faster than the rate of spontaneous ssDNA annealing under identical in vitro conditions and the reaction occurs with a high specificity in the presence of excess non-homologous ssDNA. The specificity and intrinsic nature of the reaction is also confirmed by the observation that it is stimulated by dephosphorylation of CSB, which occurs after UV-induced DNA damage, and is inhibited in the presence of ATPγS. Potential roles of CSB in cooperation with strand annealing and exchange activities for TCR and homologous recombination are discussed.